Features of trastuzumab-related cardiac dysfunction: deformation analysis outside left ventricular global longitudinal strain - Nhat, Giang M.; Hai, Nguyen H.; Duc, Vo T.; Tri, Ho H. Q.; Hoa, Chau N. (Frontiers in Cardiovascular Medicine, 2024)
Background: Cancer therapy-related cardiac dysfunction due to trastuzumab has been wellknown for many years, and echocardiographic surveillance is recommended every three months in patients undergoing trastuzumab treatment, irrespective of the baseline cardiotoxicity risk. However, the potential harm and cost of overscreening in low-and moderate-risk patients have become great concerns. Objectives: This study aimed to identify the incidence of early cancer therapy-related cardiac dysfunction (CTRCD) and the behaviours of left and right heart deformations during trastuzumab chemotherapy in low-and moderate-risk patients. Methods: We prospectively enrolled 110 anthracycline-naïve women with breast cancer and cardiovascular risk factors who were scheduled to receive trastuzumab. The left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (LV-GLS), and right ventricular and left atrial longitudinal strains were evaluated using echocardiography at baseline, before every subsequent cycle and 3 weeks after the final dose of trastuzumab. The baseline risk of CTRCD was graded according to the risk score proposed by the Heart Failure Association (HFA) Cardio-Oncology Working Group and the International Cardio-Oncology Society (ICOS). CTRCD and its severity were defined according to the current European Society of Cardiology (ESC) guidelines. Results: Twelve (10.9%) patients had asymptomatic CTRCD. All CTRCD occurred sporadically during the first 9 months of the active trastuzumab regimen in both low-and moderate-risk patients. While CTRCD was graded as moderate severity in 41.7% of patients and heart failure therapy was initiated promptly, no irreversible cardiotoxicity or trastuzumab interruption was recorded at the end of follow-up. Among the left and right heart deformation indices, only LV-GLS decreased significantly in the CTRCD group during the trastuzumab regimen. Conclusions: CTRCD is prevalent in patients with non-high-risk breast cancer undergoing trastuzumab chemotherapy. Low-and moderate-risk patients show distinct responses to trastuzumab. The LV-GLS is the only deformation index sensitive to early trastuzumab-related cardiac dysfunction.